How Large is the Corporate Tax Base Erosion and Profit Shifting? A General Equlibrium Approach - María T. Alvarez-Martínez; Salvador Barrios; Diego d'Andria; Maria Gesualdo; Gaëtan Nicodème; Jonathan Pycroft (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper estimates the size and macroeconomic effects of base erosion and profit shifting (BEPS) using a computable general equilibrium model designed for corporate taxation and multinationals. Our central estimate of the impact of BEPS on corporate tax losses for the EU amounts to exteuro36 billion annually or 7.7% of total corporate tax revenues. The USA and Japan also appear to loose tax revenues respectively of exteuro101 and exteuro24 billion per year or 10.7% of corporate tax revenues in both cases. These estimates are consistent with gaps in bilateral multinationals activities reported by creditor and debtor countries using official statistics for the EU. Our results suggest that by increasing the cost of capital, eliminating profit shifting would slightly reduce investment and GDP. It would however raise corporate tax revenues thanks to enhanced domestic production. This in turn could reduce other taxes and increase welfare.
Keywords: C68; E62; H25; H26; H87; 330; BEPS; corporate taxation; profit shifting; tax avoidance; CGE model